Assessing the rock glacier kinematics on three different timescales: a case study from the southern Swiss Alps. Issue 15 (13th June 2014) - Scapozza, Cristian; Lambiel, Christophe; Bozzini, Claudio; Mari, Stefano; Conedera, Marco
ABSTRACT Surface temperature increases since the 1990s have often been associated with an increase in the speed of rock glaciers. Evidence of similar links on the centennial to millennial scale are, however, still lacking due to less focus to date on the medium‐ and long‐term kinematics of these landforms. In order to assess (palaeo)climatic variations in rock glacier kinematics, we analysed the movements of the Stabbio di Largario rock glacier in the southern Swiss Alps using three different timescales. The Schmidt hammer exposure‐age dating (SHD) was applied to study long‐term kinematics in order to extrapolate the minimal age of the formation of the rock glacier, which may have started its development after the Mid‐Holocene climate optimum, and to detect possible accelerations of the horizontal surface velocity during the Medieval Warm Period. Georeferentiation and orthorectification of six historical photographs of the rock glacier taken between ad 1910 and today were analysed using monoplotting to detect the rock glacier displacement on the decennial scale from the end of the Little Ice Age. Finally, differential global positioning system (dGPS) monitoring data available since ad 2009 were used to assess annual and seasonal creep rates of the rock glacier at present. Our results show a link between the periods of increase in mean air temperature on different timescales and variations in rock glacier kinematics and provide important new insights into rock glacier development and evolution on the long‐term scale. Copyright © 2014 John Wiley & Sons, Ltd.